The Effect of Changes in Squish Head Angle on Compression and Torque Ratio Pressure on 160 CC Motorcycle - Aviv Rahmadillah Putra Yuslam; Sugeng Hadi Susilo; Purwoko Purwoko (Evrimata: Journal of Mechanical Engineering, 2025)
This research is to direct the mixture of air and fuel exactly to the top of the midpoint of the dome in the cylinder head. In addition, Squish Head also determines the character of the motorcycle. Moreover, what is very prominent in the initial pull is that if the compression ratio is denser, the pull is lighter.This study aims to determine the effect of changes in the slope angle of the squish head of 15, 17 and 19 degrees on compression and torque. In this study, experimental research is used with a quantitative method, where information that can be calculated and measured is factual because it is in the form of numbers. Researchers to get the data will conduct tests using the dynotest tool.Changes in slope of the squish head have an effect on the torque. At an angle of 15 degrees, torque is produced at 9.91 N.m at 6000 RPM engine rotation. At an angle slope of 17 degrees, the torque increases by 0.14 N.m to 10.05 N.m at 6000 RPM engine rotation. At an angle of 19 degrees, the torque increases by 0.17 N.m to 10.22 N.m at 6000 rpm.